2015
DOI: 10.1002/ange.201501256
|View full text |Cite
|
Sign up to set email alerts
|

Umpolung of Methylenephosphonium Ions in Their Manganese Half‐Sandwich Complexes and Application to the Synthesis of Chiral Phosphorus‐Containing Ligand Scaffolds

Abstract: Half-sandwich manganese methylenephosphonium complexes [Cp(CO) 2 Mn(h 2 -R 2 P=C(H)Ph)]BF 4 were obtained in high yield through as traightforwardr eaction sequence involving ac lassical Fischer-type manganese complex and asecondary phosphine as key starting materials.The addition of various nucleophiles (Nu) to these species took place regioselectively at the double-bonded carbon center of the coordinated methylenephosphonium ligand R 2 P + =C(H)Ph to produce the corresponding chiral phosphine complexes [Cp(CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…21 The comparison of the experimental ν C�N frequency value for [6](OTf) 2 with those of complexes [7](OTf) 2 and [8](OTf) (2206−2207 cm −1 ) revealed that the new 5,6-P,C,Cpincer ligand has similar donor character to the related 6,6membered phosphonium ylide-based analogues exhibiting NHC or phenolate donor extremities (Scheme 4). 17 These values also indicate that only pincer ligands in complexes [9](OTf) 2 (2194 cm −1 ) and [10](OTf) (2187 cm −1 ) featuring, respectively, two peripheral ylides 16a and a central ylide 23 exhibit greater electronic donation. Given that complexes [6](OTf) 2 and [7](OTf) 2 bearing neutral P,C,Cand C,C,C-pincer ligands, respectively, have the same overall charge (+2), 17 the similarity of their electronic properties is rather unexpected, taking into account the generally higher donation of NHCs vs aryl-substituted phosphines.…”
Section: ■ Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…21 The comparison of the experimental ν C�N frequency value for [6](OTf) 2 with those of complexes [7](OTf) 2 and [8](OTf) (2206−2207 cm −1 ) revealed that the new 5,6-P,C,Cpincer ligand has similar donor character to the related 6,6membered phosphonium ylide-based analogues exhibiting NHC or phenolate donor extremities (Scheme 4). 17 These values also indicate that only pincer ligands in complexes [9](OTf) 2 (2194 cm −1 ) and [10](OTf) (2187 cm −1 ) featuring, respectively, two peripheral ylides 16a and a central ylide 23 exhibit greater electronic donation. Given that complexes [6](OTf) 2 and [7](OTf) 2 bearing neutral P,C,Cand C,C,C-pincer ligands, respectively, have the same overall charge (+2), 17 the similarity of their electronic properties is rather unexpected, taking into account the generally higher donation of NHCs vs aryl-substituted phosphines.…”
Section: ■ Introductionmentioning
confidence: 85%
“…This specific arrangement results in the formation of highly constraint structures composed of two five-membered and six-membered metallacycles. In both cases, the NHC and phosphine moieties are situated in a trans position to the σ-aryl and ylide fragments, respectively [C1−Pd1−C13: [4](OTf) 173.88(10)°, [14] 16,17,23 Theoretical Study of the Electronic Structure of Pd(II) Complex 15 Bearing Two types of Phosphonium Ylide Ligands by QTAIM and ELF Topological Analyses. Since all our efforts to grow single crystals of Pd(II) complex 15 suitable for X-ray diffraction were unsuccessful, we decided to investigate its structure by DFT methods.…”
Section: X-ray Diffraction Studies Of Phosphine-nhc-phosphonium Ylide...mentioning
confidence: 99%